The Influence Of Raw Material Costs And Direct Labor Costs On Production Results (Case Study On The Sotong Duaputra Factory) - Lismandini Lismandini; Suci Putri Lestari; Barin Barlian (Journal of Indonesian Management, 2022)
This study aims to determine the effect of raw material costs and direct labor costs on production results partially or simultaneously at the Duaputra cuttlefish factory for the period 2020-2021. The data collection method in this study is an empirical study method. The data used is secondary data obtained directly from the company with data samples taken 24 months. Data analysis in this study used coefficient of determination analysis using SPSS 25 . Based on the results of this study, the cost of raw materials and direct labor costs simultaneously have a significant effect on the production at the Duaputra cuttlefish factory. The cost of raw materials partially has a significant effect on production results. Partial direct labor costs have no significant effect on production results. Therefore, it is suggested that the Duaputra cuttlefish factory can optimize its production by saving resources, so that production costs decrease and production results increase.